All-trans retinoic acid inhibits the increases in fibronectin and PAI-1 induced by TGF-β1 and Ang II in rat mesangial cells - Liu Xia; Lü Lei; Tao Bei-bei; Zhu Yi-chun (Acta Pharmacologica Sinica, 2016)
Aim: To investigate the effect of all-trans RA (atRA) on the increases in plas-minogen activator inhibitor-1 (PAI-1) and fibronectin that are induced by transforming growth factor-β1 (TGF-β1) and angiotensin II (Ang II) in cultured rat glomerular mesangial cells. Methods: Subconfluent glomerular mesangial cells were serum-starved for 48 h and pretreated with atRA with subsequent stimulation of TGF-β1 and Ang II. Protein expressions of cell-associated fibronectin and PAI-1 in glomerular mesangial cells were evaluated by Western blot analysis. mRNA expression of RA receptors in glomerular mesangial cells was examined by RT-PCR. Results: Retinoic acid receptor-α, -γ (RAR-α, -γ) and retinoid X receptor-α, -β, -γ (RXR-α, -β, -γ) mRNA were expressed in rat glomerular mesangial cells. atRA pretreatment effectively reduced fibronectin expression in glomerular mesangial cells stimulated with TGF-β1 or Ang II for 48 h. TGF-β1 stimulated PAI-1 expression reached a maximum at 5 h. atRA didn't affect the early (5 h) PAI-1 induction by TGF-β1, but markedly attenuated the sustained (48 h) PAI-1 induction. atRA also decreased the prolonged effect of Ang II on PAI-1 expression. Conclusion: These results indicate that atRA inhibits the increases in fibronectin that are induced by TGF-β1 and Ang II in cultured glomerular mesangial cells. The data also suggest that this effect of atRA is associated with a change in PAI-1 levels.